Rhodococcus equi: an animal and human pathogen. - Prescott, J F (1991)
Recent isolations of Rhodococcus equi from cavitatory pulmonary disease in patients with AIDS have aroused interest among medical microbiologists in this unusual organism. Earlier isolations from humans had also been in immunosuppressed patients following hemolymphatic tumors or renal transplantation. This organism has been recognized for many years as a cause of a serious pyogranulomatous pneumonia of young foals and is occasionally isolated from granulomatous lesions in several other species, in some cases following immunosuppression. The last decade has seen many advances in understanding of the epidemiology, pathogenesis, diagnosis, treatment, and immunity to infection in foals. The particular susceptibility of the foal is not understood but can be explained in part by a combination of heavy challenge through the respiratory route coinciding with declining maternally derived antibody in the absence of fully competent foal cellular immune mechanisms. R. equi is largely a soil organism but is widespread in the feces of herbivores. Its growth in soil is considerably improved by simple nutrients it obtains from herbivore manure. About one-third of human patients who have developed R. equi infections had contact in some way with herbivores or their manure. Others may have acquired infection from contact with soil or wild bird manure. R. equi is an intracellular parasite, which explains the typical pyogranulomatous nature of R. equi infections, the predisposition to infection in human patients with defective cell-mediated immune mechanisms, and the efficacy of antimicrobial drugs that penetrate phagocytic cells.